Piper sarmentosum as an antioxidant: a systematic review - Siti Marjiana Ismail,; Chua, Kien Hui; Amilia Aminuddin,; Azizah Ugusman, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Piper sarmentosum (PS) is an herb with various medicinal properties. The antioxidant activity of PS contributes to many of its pharmacological effects such as anti-hypertension, anti-cancer and anti-diabetes. This systematic review provides information regarding the antioxidant activity of PS. The review was conducted systematically to identify relevant published articles on the antioxidant activity of PS. The collected data was based on the searched articles through PubMed, Science Direct and Scopus databases between the years 1946 until March 2018. Only articles written in English and related to antioxidant activity of PS were included in this review. Based on the literature searched, 130 potential articles were identified and 19 articles met the inclusion criteria. Ten studies related to chemical assays, five studies combined in vivo animal and chemical assays, three studies combined chemical assays and in vitro studies and a single study combined chemical assay, in vitro and in vivo studies were included in this review. All studies showed positive effects of PS against oxidation, indicating the potential of PS as a source of natural antioxidant.